Screening Specific Biomarkers of Herbs Using a Metabolomics Approach: A Case Study of Panax ginseng - Hong-ping Wang (Nature Portfolio, 2017)
Abstract Medicinal herbs belonging to the same genus are always easily confused due to their extremely similar morphology and metabolites. Previously, to differentiate them, inherently specific biomarkers were screened out via intuitive comparison of their metabolite profiles. Unfortunately, the selected biomarkers have worked only partially. Most significant specific biomarkers have been neglected. Herein, a novel method for screening specific biomarkers of medicinal herbs using a metabolomics technique was developed. Firstly, the profiles of a group of easily confused herbs belonging to the same genus were analyzed by ultra-high performance liquid chromatography coupled with high-resolution mass spectrometry to detect all components, including low-response metabolites. Then, all components were compared between the different samples, and specific biomarkers were extracted by the metabolomics techniques of alignment, normalization, defining the sample sets, filtering by frequency and Venn diagram analysis with Mass Profiler Professional (MPP) software. Thirdly, the correlations of these biomarkers were investigated via partial correlational analysis to obtain the most representative specific biomarkers. As an example, selection of specific biomarkers for ginseng (Panax ginseng) was performed, and three specific biomarkers including chikusetsusaponin IVa, ginsenoside Rf and ginsenoside Rc were finally selected and verified as the most representative specific biomarkers of Panax ginseng.